ICTV Virus Taxonomy Profile: Hypoviridae - Suzuki, Nobuhiro; Ghabrial, Said A; Kim, Kook-Hyung; Pearson, Michael; Marzano, Shin-Yi L; Yaegashi, Hajime; Xie, Jiatao; Guo, Lihua; Kondo, Hideki; Koloniuk, Igor; Hillman, Bradley I; Ictv Report Consortium (Journal of general virology, 2018)
The Hypoviridae, comprising one genus, Hypovirus, is a family of capsidless viruses with positive-sense, ssRNA genomes of 9.1-12.7 kb that possess either a single large ORF or two ORFs. The ORFs appear to be translated from genomic RNA by non-canonical mechanisms, i.e. internal ribosome entry site-mediated and stop/restart translation. Hypoviruses have been detected in ascomycetous or basidiomycetous filamentous fungi, and are considered to be replicated in host Golgi-derived, lipid vesicles that contain their dsRNA as a replicative form. Some hypoviruses induce hypovirulence to host fungi, while others do not. This is a summary of the current ICTV report on the taxonomy of the Hypoviridae, which is available at www.ictv.global/report/hypoviridae.
Keywords: RNA, Viral; Phylogeny; dvouvláknová RNA; Fungi; Open Reading Frames; RNA, Double-Stranded; RNA-viry; genom virový; RNA virová; houby; RNA Viruses; otevřené čtecí rámce; Genome, Viral; fylogeneze